An Innovative IoT-Based Intelligent Control System for Agricultural Greenhouses - Zhong, Xiaolei; Qiao, Rui; Wang, Xin (International Journal of Mechanical and Electrical Engineering, 2024)
As the material living standards of residents rapidly improve, the demand for fruits and vegetables continues to rise. Agricultural greenhouses, as a critical means of increasing fruit and vegetable yields, require effective control of temperature, humidity, and light intensity to ensure rapid crop growth. Traditional manual monitoring and control methods are inefficient and labor-intensive. Against the backdrop of rapid developments in electronic technology, this paper innovatively designs a greenhouse IoT intelligent control system based on a microcontroller, achieving real-time monitoring and automated control of greenhouse environment parameters. The innovations of this system are evident in several aspects: Firstly, it employs an STM32 microcontroller as the main control chip, integrating YL-69 soil moisture sensors, GL5506 photodiodes, and DS18B20 temperature sensors to achieve high-precision detection of soil moisture, light intensity, and temperature. Secondly, an LCD1602 display is used to timely showcase real-time environmental parameters, and alarm thresholds can be set via buttons. If these thresholds are exceeded, a buzzer sounds an alarm. Concurrently, the system utilizes water pumps and supplementary LED lights to intelligently adjust humidity and light intensity within the greenhouse. Most importantly, by incorporating the ESP8266 module, the system achieves remote data transmission, allowing users to view real-time environmental parameters via a mobile app and set thresholds and control operations. This greenhouse IoT intelligent control system not only features alarm functions for exceeded environmental parameters but also enables automatic adjustment through intelligent devices and supports remote control, greatly enhancing operational convenience and system practicality. Overall, this system innovatively integrates various sensing technologies and IoT communication, providing an efficient and intelligent solution for the modern management of agricultural greenhouses. It exhibits broad market prospects and holds significant importance for advancing agricultural modernization.